Perfil farmacoterapêutico de adolescentes usuários de um centro de atenção psicossocial álcool e drogas infanto juvenil do estado de Goiás - Araújo, Sandra Hernandez Morais de (2017)
Introduction: The use of Psychoactive Substances (PS) brings problems in several areas of the subject's life such as: health, psychological and social. Epidemiological studies show that it is in the passage from childhood to adolescence that the use begins. In Brazil, the treatment is preferentially done in the Centers of Psychosocial Care and in them are offered psychosocial and pharmacological interventions and the combination of them. Pharmacological interventions can be used to stabilize, detoxify, ameliorate withdrawal symptoms and prevent relapse. The pharmacist plays an important role in the safe and effective use of medicines in children and adolescents, since it can prevent identifying, evaluating and intervening in problems related to pharmacotherapy. Objective: to analyze the use of drugs by users of the Psychosocial Care Center Alcohol and Drugs Infanto Juvenil 24 hours (CPCAD adi III). Methodology: an analytical and quantitative cross-sectional study, carried out by reviewing medical records. The medical records of users who were younger than 18 years of age and with prescription of medicines were included and the medical records that were not filled out were excluded. Potential drug interactions (PDI) were analyzed using the Micromedex® and Medscape® database. Descriptive and bi-and multivariate logistic regression analyzes were performed considering a statistically significant relationship p≤0.5. Results: Of the 159 records used in the study, 71.7% were male subjects with mean age of 16 ± 1.9 years, incomplete elementary schooling (88%) and the search for treatment occurred in 55, 3% by judicial measure. Among the diagnostic hypotheses, the most frequent were mental and behavioral disorders due to the use of multiple drugs and the use of other psychoactive substances (F19) 34.9% and mental and behavioral disorders associated with the use of cannabinoids (F12) With 17.2%. The age of first use of SP was on average 12.4 ± 1.90 years. The most used PS was Cannabis (37.2%). The most prescribed drugs were the N03A (antiepileptic) 39.94% and N05A (antipsychotic) 34.83%% groups. A total of 815 PDI were found per type of interaction, 352 drugcannabis, 139 drug-ethanol, 125 drug-foods, 99 drug-tobacco, 83 drug-drug, and 17 drug-cocaine. Regarding the severity of the PDI found, 59.4% were moderate, 23.8% were secondary, 15.7% were serious and 1.1% were contraindicated. The drugs that presented the most PDI were chlorpromazine (32.3%) and diazepam (19.6%). Conclusion: the adolescents were the majority of males, the diagnostic hypothesis that had the highest frequency was that of mental and behavioral disorder due to the use of SPA (F-19). The use of PS was on average at 12 years of age and the most consumed PS was marijuana. The most commonly prescribed drugs were valproic acid (30.63%) and chlorpromazine (20.72%). It was found of 815 PDI with 59.4% classified as moderate. The factor involved in polypharmacy was total PDI and among the factors involved in the occurrence of total PDI were: being studying and the amount of diagnostic hypothesis. In view of the high PDI index, the relationship with polypharmacy and a high number of diagnostic hypotheses, it is necessary to increase the attention of health professionals regarding the topic and the development of protocols to support decision making.